The Effect of Moringa oleifera's antibacterial and antibiofilm properties against Fusobacterium nucleatum and Staphylococcus aureus: an experimental study - Fernando, Theodorus Aldo; Amin, Meiny Faudah; Ariwibowo, ⁠Taufiq; Binartha, Ciptadhi Oka; Kurnia, Dikdik (Universitas Padjadjaran, 2025)
Introduction: Fusobacterium nucleatum and Staphylococcus aureus, both associated with pulp and periapical diseases, must be effectively eliminated during irrigation. Natural agents are generally more biocompatible and less harmful to bodily tissues, making them a promising alternative to chemical irrigants such as sodium hypochlorite. Fractions of Moringa oleifera have demonstrated potential as an alternative irrigant due to their antibacterial and antibiofilm properties. This study aimed to analyze the antibacterial and antibiofilm efficacy of Moringa oleifera fractions against Fusobacterium nucleatum and Staphylococcus aureus. Methods: The tube dilution method was used for antibacterial tests, while the biofilm assay method measured the optical density (OD) in a 96-well plate to evaluate antibiofilm effects against Fusobacterium nucleatum ATCC 25586 and Staphylococcus aureus ATCC 25923. Moringa oleifera fractions were tested at 20%, 40%, 60%, and 80% concentrations. A one-way ANOVA test was applied for normally distributed data, and the Kruskal Wallis test was used for non-normally distributed data. Post-hoc analyses were conducted to determine significant differences between groups, with the significance level set at 0.05. Results: The antibacterial test revealed statistically significant differences between Moringa oleifera groups in eliminating Fusobacterium nucleatum (p=0.003, p<0.05) and Staphylococcus aureus with p value (p=0.001, p<0.05). The antibiofilm test also showed statistically significant differences among the concentration groups for both bacteria. Conclusion: The antibacterial and antibiofilm effectiveness of Moringa oleifera’s fractions against Fusobacterium nucleatum and Staphylococcus aureus, supporting its potential as an alternative irrigant.